USE OF METABOLOMICS TO THE DIAGNOSIS OF INFLAMMATORY BOWEL DISEASE - Manoel Álvaro de Freitas LINS NETO; Giulia Maria Ximenes VERDI; Arthur de Oliveira VERAS; Matheus de Oliveira VERAS; Luiz Carlos CAETANO; Jeferson Santana URSULINO (Arquivos de Gastroenterologia, 2020)
ABSTRACT BACKGROUND: Crohn’s disease and ulcerative colitis are the primary inflammatory bowel diseases (IBD), and its pathogenesis is related to genetic and environmental factors. Currently, the diagnosis of IBD results in a multidisciplinary approach with significant disadvantages, such as its invasive nature, time spent, and the fact that 10% of patients remain without diagnostic classification. However, new methodologies of analysis have emerged that allowed the expansion of knowledge about IBD, as the metabolomics, the study of metabolites. The presence and prevalence of such metabolites may prove to be useful as biomarkers in the diagnosis of IBD. OBJECTIVE: Analyze fecal samples for metabolic analysis in the diagnosis of inflammatory bowel diseases (IBD), providing differentiation between Crohn’s disease and ulcerative colitis. METHODS: This is an observational study with 21 patients diagnosed with IBD (ulcerative colitis 11 and Crohn’s disease 10) and 15 healthy controls, all with the consent and clarification. The fecal extracts of all patients are submitted to a high-resolution Nuclear Magnetic Resonance Hydrogen (1H-NMR) spectroscopy combined with multivariate and univariate pattern recognition techniques. Through the metabolomics of fecal extracts, gives us a characterization of employing a noninvasive approach. RESULTS: We identify some metabolites, such as lactate, succinate, alanine, and tyrosine, in the Crohn’s disease fecal samples, and leucine, alanine, and tyrosine in the ulcerative colitis fecal samples. All the amino acids presented positive covariance for disease correlation. CONCLUSION: The results showed different metabolic profiles between IBD patients and healthy volunteers based on 1H-NMR analysis of fecal extracts. Moreover, the approach discriminated patients with Crohn’s disease and ulcerative colitis. The metabolomics analysis is promising as a novel diagnostic technique for further IBD recognition and surveillance. New studies are necessary to validate these findings.